ASOSIASI GASTROPODA DENGAN TUMBUHAN MANGROVE PADA EKOSISTEM PANTAI DI NEGERI TIOUW DAN NEGERI HARIA KECAMATAN SAPARAUA KABUPATEN MALUKU TENGAH - Linus Takandare; Pamela Mercy Papilaya (Program Studi Pendidikan Biologi FKIP Unpatti, 2018)
Background: Mangrove forests are one of the unique natural ecosystems with high ecological value. Mangrove ecosystems are one of the areas with high productivity because there are litter and decomposition of litter and detritus occurs. This study was conducted to determine the association between gastropods and mangrove plants. Method: Research on gastropod association with mangrove plants in the coastal waters of Tiouw Village and Haria Village was conducted in January 2018. Results: This study found from gastropods 6 species namely variabilis strombus, microurceus strombus, Nassarius luridus, Strombus urceus, Cypraea annulus, Strombus, Strombus, Nerita squamulata. From the mangrove plants, 10 species were found: Avicennia eucalyptifolia, Avicennia lanata, Bruguiera sexangula, Rhizophora apiculata, Bruguiera hainessi, Aegiceras floridum R, Aegiceras curniculatum L, Bruguiera palviflora, Bruguiera exaristafa, Ceriops tagal. Conclusion: Association values ​​ranged from 0.741-0.9773 with positive and negative types. This means that both types of seagrass are often found together or not found together in the observation location